Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya di PGMI 3 UINSU - Purba, Hilda Melani; Wandini, Rora Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Misconceptions can simply be defined as misunderstanding or misunderstanding. In misconception, there is a conflict or incompatibility between the concepts understood by a person and the concepts used by experts or specialists in that field of science. The occurrence of misconceptions in a person can be due to inaccurate understanding of concepts, use of incorrect concepts, incorrect classification of examples, confusion between different concepts, and incorrect relationship between concept hierarchies. The aim of this research is to examine or find out the results of the analysis of misconceptions in understanding plane material by applying Polya theory at PGMI 3 UINSU. This research uses observation methods and problem-solving tests to identify misconceptions that occur or arise when PGMI-3 students work on flat shape material with the application of polya theory. The results of this research show that there are several misconceptions involving understanding each step in Polya's theory. The steps are understanding, planning, implementing and assessing. The occurrence of misconceptions in Polya's theory mostly starts from the planning and implementation steps, where the symbols for a flat shape and also the cm symbol are not used in problems whose length or width is known. Most of the causes of this misconception are related to inaccurate understanding and lack of focus on the steps in Polya's theory. The mistake that many students make is the error in determining the steps of Polya's theory. The results provide important insights for curriculum development and more effective teaching approaches in understanding plane material by applying Polya's theory. This research also has implications in the broader context of mathematics education in Indonesia.